Holiday Inn [videorecording (DVD)] - Crosby, Bing, 1903-1977; Astaire, Fred; Reynolds, Marjorie, 1917-1997 (Universal Pictures Home Entertainment, 2017)
Screen legends Bing Crosby and Fred Astaire sing and dance in one of the most timeless holiday classics of all time. Featuring the Academy Award-winning song, "White Christmas", Crosby plays a song and dance man who leaves showbiz to run an inn that is open only on holidays. Astaire plays his former partner and rival in love. Follow the two talented pals as they find themselves competing for the affections of the same lovely lady.